The Influence of the Motivation and Work Environment on the Performance of Experts of the House of Representatives of the Republic of Indonesia - Fauzobihi, Fauzobihi; Sugiatno, Sugiatno; Ismuni, Mutdi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The House of Represe natives of the Republic of Indonesia (House of Representatives of the Republic of Indonesia) is one of the highest state institutions in the Indonesian constitutional system. The House of Representatives of the Republic of Indonesia functions as the people's representative who has the authority to make laws, supervise the implementation of laws, and give approval to the budget proposed by the government. The method used in this study is descriptive. The population in this study is the entire workforce of the House of Representatives of the Republic of Indonesia and the research sample is 50 Expert Workers of the House of Representatives of the Republic of Indonesia. The research was carried out by distributing questionnaires of 10 questions on variable X and 10 questions on variable Y.